Spinning Yarns: Bengal Textile Industry in the Backdrop of John Taylor’s Report on ‘Dacca Cloth Production’ (1801), 1st edition - Chaudhury, Sushil (Routledge, 2020)
Since time immemorial Indian textiles, especially textiles from Bengal, were in great demand and exported to different parts of the world. Textiles from Bengal were appreciated by the Romans as early as first century ad. Numerous foreign travellers including Chinese, Portuguese, Arab and Persian, have mentioned the delicacy and beauty of Bengal textiles. From the mid-seventeenth century, there was a massive spurt in demand of cloth manufactured in Bengal, but after the British conquest of Bengal in 1757 this industry started to decline.